1999
DOI: 10.1111/j.1469-8749.1999.tb00664.x
|View full text |Cite
|
Sign up to set email alerts
|

Sensory‐modulation disruption, electrodermal responses, and functional behaviors

Abstract: It was hypothesized that children clinically identified with sensory‐modulation disruptions (SMD) would have atypical physiological responses to sensation, and that such responses would predict parent‐reported behavioral responses to sensation. Nineteen children with clinically identified disruptions, aged 3 to 9 years, mean 6.0 years, and 19 age‐and sex‐matched healthy (control) children, aged 3 to 9 years, mean 6.6 years, were examined. The subjects were presented with five stimuli. Ten trials were conducted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0
3

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 22 publications
2
32
0
3
Order By: Relevance
“…This result is consistent with the first psychophysiological studies conducted using infants and young children with RD symptoms, in which different patterns of physiological reactivity were observed in relation to normally developing children [22,47]. The results of this study also agree with those of psychophysiological studies that have compared children who have sensory modulation dysfunction (SMD) with normally developing children, with findings such as a higher frequency and amplitude in skin conductance [15], different event-related potential patterns [14], and increased parasympathetic responses [16] with regard to task performance in children with SMD.…”
Section: Discriminative Sensory Symptoms Of Rdsp Versus Those Of Od3rsupporting
confidence: 91%
See 1 more Smart Citation
“…This result is consistent with the first psychophysiological studies conducted using infants and young children with RD symptoms, in which different patterns of physiological reactivity were observed in relation to normally developing children [22,47]. The results of this study also agree with those of psychophysiological studies that have compared children who have sensory modulation dysfunction (SMD) with normally developing children, with findings such as a higher frequency and amplitude in skin conductance [15], different event-related potential patterns [14], and increased parasympathetic responses [16] with regard to task performance in children with SMD.…”
Section: Discriminative Sensory Symptoms Of Rdsp Versus Those Of Od3rsupporting
confidence: 91%
“…Relatedly, several studies have noted the phenotypic similarities between RDSP and other diagnoses in toddlers [7,10,[13][14][15][16] such as anxiety [17] or other emotional problems [18], Autism Spectrum Disorders (ASD) [13] and other ''relationship-based diagnoses'' [19]. This similarity has led researchers to question whether RDSP symptoms can help to distinguish RDSP from the other psychiatric disorders that affect children [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Also, children may respond differently to sensory experiences in different modalities. Some research suggests that a general sensory modulation disorder underlies symptoms of both tactile and auditory defensiveness (McIntosh, Miller, Shyu, & Hagerman, 1999), but the specificity issue remains open. Again, knowing if one type of sensory defensiveness shares genetic variance with another could add to our understanding of the relationship between the two sensory domains.…”
Section: Association Of Sensory Defensiveness With Other Childhood Bementioning
confidence: 99%
“…This study asserted that over-reactivity in the area of auditory defensiveness as well as the tactile area had a greater association with emotional symptoms than other sensory areas (Ben-Sasson et al 2009). Other studies, which compared sensory modulation deficits between children with SPD and children with no diagnosis (McIntosh et al 1999b), found the greatest differences between groups in regards to the auditory area. The lack of significant differences in other sensory areas in the current study may be related to sample size and/or the sample origin.…”
Section: Discussionmentioning
confidence: 91%
“…In order to assess sensory modulation deficits in infants and toddlers, Dunn (2001) developed the Infant/ Toddler Sensory Profile schedule. Dunn's model has evidence of external validity due to the significant association between the electrodermal responses given by children with and without SMD or different sensory patterns of the short sensory profile (SSP) (McIntosh et al 1999b;Schaaf 2001) as well as the discriminant capacity of the clinical samples (Dunn 2001).…”
Section: Introductionmentioning
confidence: 99%